KARAKTERISTIK PERJALANAN DAN PEMILIHAN MODA TRANSPORTASI PADA KONDISI COVID-19 DI WILAYAH AGLOMERASI SURAKARTA - Budiarto, Arif (Prodi Teknik Sipil Fakultas Teknik Universitas Sebelas Maret Surakarta, 2024)
The COVID-19 pandemic, which spread to all countries worldwide, also influenced changes in individual behaviors related to activities and travel. These changes were further intensified by government policies to implement lockdowns to reduce the spread of the Coronavirus. The impact of these policies resulted in a significant decrease in the frequency of public travel, resulting in the preference for the use of private vehicles to avoid Coronavirus transmission. This study was conducted to investigate individual travel behavior in the Surakarta Agglomeration Area. Data were collected through home interview surveys from March to June 2021, involving 402 respondents. It was hypothesized that with regard to sociodemographic attributes, those with high-income levels would rely more on private vehicles during the COVID-19 pandemic, while lower-income groups would show the opposite trend. The results of the study indicated that high-income individuals were highly dependent on private vehicles, particularly cars, compared to those with other attributes. 17.8% of high-income respondents used cars more frequently than those in other income groups, finding them not only safer from COVID-19 transmission but also more comfortable.